Enabling a Nationwide Radio Frequency Inventory Using the Spectrum Observatory - Zheleva, Mariya; Chandra, Ranveer; Chowdhery, Aakanksha; Garnett, Paul; Gupta, Anoop; Kapoor, Ashish; Valerio, Matt (Transactions of Mobile Computing, 2018)
Knowledge about active radio transmitters is critical for multiple applications: spectrum regulators can use this information to assign spectrum, licensees can identify spectrum usage patterns and provision their future needs, and dynamic spectrum access applications can efficiently pick operating frequency. To achieve these goals, we need a system that continuously senses and characterizes the radio spectrum. Current measurement systems, however, do not scale overtime, frequency and space and cannot perform transmitter detection. We address these challenges with the Spectrum Observatory, an end-to-end system for spectrum measurement and characterization. This paper details the design and integration of the Spectrum Observatory, and describes and evaluates the first unsupervised method for detailed characterization of arbitrary transmitters called TxMiner. We evaluate TxMiner on real-world spectrum measurements collected by the Spectrum Observatory between 30 MHz and 6 GHz and show that it identifies transmitters robustly. Furthermore, we demonstrate the Spectrum Observatory's capabilities to map the number of active transmitters and their frequency and temporal characteristics, to detect rogue transmitters, and identify opportunities for dynamic spectrum access.